DEVELOPMENT OF A DECISION SUPPORT SYSTEM FOR EVALUATING INVESTMENT PROJECTS TAKING INTO ACCOUNT MULTI-FACTORITY BASED ON THE METHOD OF HIERARCHY ANALYSIS AND GAME THEORY (Journal of Mathematics Mechanics and Computer Science, 2021)
The paper describes the developed software product-the decision support system (DSS) «DSS Invect 2020» and its module «IT INVESTMENT», which can be used both independently and as part of the DSS «DSS Invect 2020». The DSS is designed to make recommendations to the DSS during the selection of rational financial strategies by investors. «DSS Invect 2020» allows you to evaluate the attractiveness of investment projects in the field of digitalization of enterprises. The DSS «DSS Invect 2020» is implemented on a modular basis. This makes it possible to supplement the DSS with other modules.
Keywords: decision support system; investment project; software product; module